Natural ingredients in cosmetics from Malaysian plants: a review - Hasmida Mohd-Nasir,; Siti Hamidah Mohd-Setapar, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Consumer consciousness on the concept of natural-based ingredients triggers the natural cosmetics market to grow. The active compounds in natural ingredients offer valuable bioactivities such as antioxidant, photoprotection, anti-aging and anti-inflammatory actions that useful for skincare, hair care and dental care. This review presents an overview on natural ingredient, especially plant-derived, used in cosmetic products and the examples of Malaysian plants used for cosmetic purposes.